Pengaruh Tingkat Pengungkapan Corporate Social Responsibility terhadap Information Asymmetry dengan Variabel Kontrol Beta dan Managerial Ownership - Sylvia Adriani; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to identify and to prove the affect of Corporate Social Responsibility disclosure level to information asymmety. Corporate Social Responsibility disclosure of companies measured by using level of Corporate Social Responsibility disclosure which assessed by using criteria guidelines of GRI Index. Information asymmetry in this study was measured by using bid-ask spread. This study also used control variables: beta and managerial ownership. This research was carried on go public companies in Indonesia which published sustainability reporting and listed in GRI’s database with a sample of 130 observations. The results of this study showed that there was a significant positive affect of Corporate Social Responsibility on bid-ask spread. The results also showed that beta had no affect on bid-ask spread, while managerial ownership had significant positive affect on the bid-ask spread.